The myth of Mondragón : cooperatives, politics, and working-class life in a Basque town - Kasmir, Sharryn (SUNY series in the anthropology of work., 1996)
"This is the first critical account of the internationally renowned Mondragon cooperatives of the Basque region of Spain. The Mondragon cooperatives are seen as the leading alternative model to standard industrial organization; they are considered to be the most successful example of democratic decision making and worker ownership. However, the author argues that the vast scholarly and popular literature on Mondragon idealizes the cooperatives by falsely portraying them as apolitical institutions and by ignoring the experiences of shop floor workers. She shows how this creation of an idealized image of the cooperatives is part of a new global ideology that promotes cooperative labor-management relations in order to discredit labor unions and working-class organizations; this constitutes what she calls the "myth" of Mondragon."--Jacket